The effectiveness of seed coating with microbial fungicide on controlling seed quality and damping-off disease of tomato - S. Baikaden; P. Sikhao; Prommart Koohakan (International Journal of Agricultural Technology, 2026)
Microbial seed coating was not significantly influenced germination percentage, germination index, or germination speed under laboratory conditions. Whereas, seeds coated with Trichoderma asperellum and Bacillus subtilis consistently demonstrated to improve seedling emergence and vigor in greenhouse conditions. With respect to disease suppression, coatings seeds with T. asperellum resulted to reduce both the incidence and severity of damping-off disease caused by Pythium torulosum. The lowest disease incidence (30.50%) and severity (17.43%) were observed in seedlings from T. asperellum-coated seeds. These findings highlighted the potential of antagonistic microbial coatings to promote seedling health and provided a sustainable strategy for managing soilborne diseases. This approach is offered a promising complement or alternative to chemical control methods in commercial tomato seedling production.
Keywords: Plant-Microbe Interactions and Immunity; Agriculture, Plant Science, Crop Management; Nanocomposite Films for Food Packaging